The role of flipped learning techniques in increasing students' motivation to learn economics (Journal of Imam Al-Kadhim College, 2023)
Abstract:This study aimed to explore the role of reverse learning techniques in increasing students' motivation to learn management and economics subjects from the perspective of teachers in the General Directorates of Education in Baghdad Governorate. The study employed a descriptive-analytical methodology and was applied to a random sample of 120 teachers of management and economics subjects. The results indicated that the sample respondents' overall scores on the questionnaire assessing the role of reverse learning techniques in increasing students' motivation to learn management and economics subjects were moderate. Furthermore, statistically significant differences were found in the average scores of the sample respondents on the overall questionnaire, attributed to the variables of academic qualification and years of experience. However, there were no statistically significant differences in the average scores of the sample respondents on the overall questionnaire attributed to the variable of gender. The study recommended several recommendations, the most important of which included organizing workshops and seminars for educational professionals and the local community to respond to recent scientific developments, particularly the strategy of reverse learning. It also recommended that parents follow up on their children's use of technology to enhance their skills development and address any deficiencies in their scientific knowledge.
Keywords: Reverse learning strategy, motivation, teachers of economics.